Investigation of nonlinear distortion in double heterojunction GaAs based pHEMT subject to frequency and temperature - Alim, Mohammad A.; Ali, Mayahsa M.; Rezazadeh, Ali A. (Solid-state electronics, 2018)
•Nonlinearity study of double heterojunction GaAs pHEMT using a two-tone technique.•Effect of biasing conditions, input power, frequency and temperature on fundamental, IMD2, IMD3, IMD4, IMD5 and IMD7.•Increase in input power resulting to an increase in the output IMD power.•Increase in frequency & temperature reduces the magnitude of the output IMDs.•The notch position of nonlinear IMDs shifts with threshold voltage change with temperature. Linear and nonlinear characteristics of a 0.5 μm × (2 × 100) μm gate double heterojunction AlGaAs/InGaAs/GaAs pseudomorphic high-electron mobility transistor have been investigated using a two-tone intermodulation distortion (IMD) measurement technique. The results indicate a significant modification on the IMD output power components such as fundamental, IMD2, IMD3, IMD4, IMD5 and IMD7 with the variation of biasing conditions, input power, frequency and temperature. Increase in input power affects the output current as well as the parasitic resistances and subsequently the threshold voltage reduces, resulting to an increase in the output IMD power. On the other hand, increase in frequency & temperature reduces the magnitude of the output IMDs. The temperature affects the output current as well as the parasitic resistances and the threshold voltage, results a decrease in the output IMD power. The threshold voltage shifts negatively with temperature and modifies the notch/null’s position of the second and higher order IMD output power components. This investigation is valuable for the circuit designers to evaluate the best biasing option in terms of minimum distortion, maximum gain for future design optimizations.